EurOOHnet—the European research network for out-of-hours primary health care. (September 2014) - Huibers, Linda; Philips, Hilde; Giesen, Paul; Remmen, Roy; Christensen, Morten Bondo; Bondevik, Gunnar Tschudi
Abstract Background and rationale: European countries face similar challenges in the provision of health care. Demographic factors like ageing, population growth, changing patient behaviour, and lack of work force lead to increasing demands, costs, and overcrowding of out-of-hours (OOH) care (i.e. primary care services, emergency departments (EDs), and ambulance services). These developments strain services and imply safety risks. In the last few decades, countries have been re-organizing their OOH primary health care services. Aim and scope of the network: We established a European research network for out-of-hours primary health care (EurOOHnet), which aims to transfer knowledge, share experiences, and conduct research. Combining research competencies and integrating results can generate a profound information flow to European researchers and decision makers in health policy, contributing towards feasible and high-quality OOH care. It also contributes to a more comparable performance level within European regions. Conducted research projects: The European research network aims to conduct mutual research projects. At present, three projects have been accomplished, among others concerning the diagnostic scope in OOH primary care services and guideline adherence for diagnosis and treatment of cystitis in OOH primary care. The future: Future areas of research will be organizational models for OOH care; appropriate use of the OOH services; quality of telephone triage; quality of medical care; patient safety issues; use of auxiliary personnel; collaboration with EDs and ambulance care; and the role of GPs in OOH care.